2011
DOI: 10.1158/1541-7786.mcr-10-0272
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Dipeptidyl Peptidase 9 in Epidermal Growth Factor Signaling

Abstract: Dipeptidyl peptidase IV (DPP4), DPP8, DPP9, and fibroblast activation protein (FAP), the four proteases of the DPP4 gene family, have unique peptidase and extra-enzymatic activities that have been implicated in various diseases including cancers. We report here a novel role of DPP9 in regulating cell survival and proliferation through modulating molecular signaling cascades. Akt (protein kinase B) activation was significantly inhibited by human DPP9 overexpression in human hepatoma cells (HepG2 and Huh7) and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 38 publications
3
63
1
Order By: Relevance
“…In all cell lines analyzed in our study, we observed no correlation between the endogenous expression of DP8 and DP9 mRNA and protein. This is consistent with the Yao et al observation of no change in DP8 protein expression following heterologous overexpression of DP9 in HEK293T and HepG2 cells (36).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In all cell lines analyzed in our study, we observed no correlation between the endogenous expression of DP8 and DP9 mRNA and protein. This is consistent with the Yao et al observation of no change in DP8 protein expression following heterologous overexpression of DP9 in HEK293T and HepG2 cells (36).…”
Section: Discussionsupporting
confidence: 93%
“…However, information on the expression of DP8 and DP9 in pathophysiological settings and potential roles in cancer is limited. In contrast to the recently identified NPY-dependent survival role suggested for DP8/DP9 in Ewings sarcoma (16), the overexpression of DP8 and DP9 in HEK293T and HepG2 cells has been shown to increase migration, proliferation and enhance staurosporine-streptomyces induced apoptosis (17,36) suggesting the effects of DP8/DP9 in cancer, like DP4 and FAP, may be tumor specific. In chronic lymphocytic leukemia (CLL) a significant increase in DP8 mRNA has been observed (37) while upregulation of DP9 mRNA has been observed in testicular cancer (38).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Additionally, the inhibition of intracellular DPP9 enhances the anti‐leukemic activity of parthenolide,28 while DPP9 may also act as a survival factor for cells from the Ewing's sarcoma family of tumors cells and protect them against cell death induced by endogenous neuropeptide Y 29. On the other hand, DPP9 overexpression was reported to inhibit phosphoinositide 3‐kinase/Akt signaling in an epidermal growth factor receptor‐dependent manner, attenuating cell proliferation and promoting apoptosis in human hepatoma cells 30. Therefore, the pro‐ or anti‐tumor activity of DPP9 may depend on the cell type and the molecular context within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%